Synthèse et étude structrale de lyonsite-type (Na(0,4),Li(0,6))(Fe,Li(2))(MoO(4))(3) - Souilem, Amira (International Union of Crystallography, 2015)

(untitled) (Acta Crystallogr E Crystallogr Commun)
The new compound (Na(0.4),Li(0.6))(Fe,Li(2))(MoO(4))(3) was synthesized by cooling from the melt. Its anionic framework is built up from two distinct MO(6) octahedra, each containing disordered Li(+) and Fe(3+) ions in 0.6:0.4 and 0.7:0.3 ratios, and two MoO(4) tetrahedra, which link by vertex-sharing of their O atoms. These tetrameric units are further linked by sharing edges between octahedra and by formation of M—O—Mo (M = Fe/Li) bridges, forming ribbons propagating in the [100] direction. The ribbons are cross-linked in both the b- and c-axis directions, giving rise to a three-dimensional framework having [100] tunnels in which the monovalent Na(+)/Li(+) cations (0.4:0.6 ratio) lie. Bond-valence calculations are consistent with the disorder model for the cations. The structure of the title compound, which is isotypic with Li(3)Fe(MoO(4))(3) and Li(3)Ga(MoO(4))(3), is compared briefly with those of LiFeMo(2)O(8) and Li(1.6)Mn(2.2)(MoO(4))(3).